Penyampaian Pesan Dakwah Ustadz Muhammad Nuzul Dzikri pada Akun Media Sosial Instagram - Maharani, Shilvia; Asia T, Nur (STAI Publisistik Thawalib Jakarta, 2024)
The da'wah activities on social media have drawn the attention of many parties, which has subsequently brought forth da'i (Islamic preachers) who utilize this platform as a means to convey Islamic teachings. This research aims to analyze the method of delivering da'wah messages employed by Ustadz Muhammad Nuzul Dzikri on his Instagram account @muhammadnuzuldzikri. The study utilizes a qualitative method, employing content analysis and direct observation of the posted content. The findings indicate that Ustadz Muhammad Nuzul Dzikri conveys his da'wah messages through the use of posters and videos on his Instagram account. The content of these messages encompasses various aspects such as creed, morality, worship, and transactions. These messages are presented with the intention of educating and inspiring his followers to live their daily lives in accordance with Islamic teachings.